Eriophyoid mites (Acari: Eriophyoidea) associated with palm trees - Navia, Denise; Gondum Junior, Manoel G.c.; de Moraes, Gilberto J. (Zootaxa, 2007)
Information is presented on eriophyoid mites found on palm trees worldwide by different authors, including original data from a recent survey conducted in Brazil, Costa Rica and Mexico. For each species, information on synonymy, locations where it was found on palm trees, palm hosts, and damage are included. Sixty-two eriophyoid species from 31 genera, associated with 54 palm tree species from 25 genera, are listed. A dichotomous key is provided to help in the separation of the reported mites. Four eriophyoid species are reported on palm trees in Europe; 6 in Africa; 17 in Asia, Pacific Islands and Australia; and 40 in the Americas. Four of the reported species belong to Diptilomiopidae, 44 to Eriophyidae and 14 to Phytoptidae. The need for further studies on these mites around the world is discussed.